Da geração de energia para o lazer: estudo da Usina Hidrelétrica de Salto Caxias/PR - seu papel econômico e social na formação de territórios - França, Francieli Mezzomo (2011)
In the path of Brazilian energy production, the dams have a leading role in the national development, but also in sociospatial transformations. This study examines the Salto Caxias Hydroelectric Power Plant, its economic and social role in the formation of territories in the urban community that had affected areas. The paper presents an overview of the Brazilian energy production and the sociospatial transformations resulting from the construction of dams, as well as a history of the Brazilian energy sector under the bias of the environmental issue. It was held a conceptual review of some geographic categories used constantly by the literature by studying tourism, such as landscape, place, space and territory, beyond the concept of leisure. Specify the tourism and recreation in the reservoirs and the production and consumption of space by their activities. The methodology used was based on the survey of literature on the topic and empirical research, through questionnaires, interviews and observations in situ. The results obtained allowed to understand the importance that the construction of the Salto Caxias dam had in the new sociospatial dynamics that originated in the urban communities affected. The tank formation as well as its use and use of its banks allowed the leisure and tourism practice in the region. The research revealed the tourism contribution of second homes for the production of space and the (re)creation of the territory.